Analysis of the implementation of Indonesia Financial Accounting Standards number 109 at the National Management Agency of West Kalimantan Province - Riyadhi, Baidhillah; Prasetyo, Henri; Fiorintari, Fiorintari (Journal of Islamic Accounting and Finance Research, 2021)
Purpose - This research aims to determine the implementation of Indonesia Financial Accounting Standards (PSAK) 109 at the National Zakat Management Agency (Baznas) of West Kalimantan Province.Method - The research was conducted using a qualitative descriptive research method to describe events in the research field, in the form of reports and distribution of Zakat, Infaq and Shadaqah (ZIS) in 2017 and 2018, then compared with PSAK 109. Â Â Result - The results showed that the implementation of PSAK 109 in the recognition and measurement section of Baznas in West Kalimantan Province can be stated in accordance with PSAK 109. Meanwhile, the implementation of PSAK 109 in the presentation, disclosure and component of financial statements in Baznas of West Kalimantan Province has not fully implemented PSAK 109 as a whole.Implication - The implication of this research is expected to help Baznas of West Kalimantan Province in implementing PSAK 109 so that public trust can increase in the management of ZIS funds.Originality - The uniqueness of this research compared to several previous researches can be seen from the object of research that was first conducted at Baznas of West Kalimantan Province and the research used the data in the last 2 years.